A BSP realisation of Jarvis' algorithm - Cinque, L.; Di Maggio, C. (Pattern recognition letters, 2001)
The purpose of this paper is to present a very efficient parallel algorithm for computing the convex hull in the plane. We propose a parallel version of the Jarvis' march, realised using the bulk synchronous parallel (BSP) model and which takes O( nh/ p) time (where p is the number of processors, h the number of vertices of the convex hull and n is the problem size) against the O( nh) complexity of the sequential algorithm. Furthermore, we give the experimental results obtained testing the algorithm implementation on a 16-node IBM Scalable POWERparallel 2 (SP2) and we compare them with the theoretical performance prediction obtained using the BSP cost calculus model.